Association of the 65-bp indel polymorphism in \(GOGLB1\) gene with body weight of Vietnamese Noi chickens - Dieu Thuy, Nguyen Thi; Quynh Mai, Vu; Anh Khoa, Do Vo (Academia Journal of Biology, 2023)
Noi chicken is one of the indigenous fighting-cock breeds of Vietnam with many valuable properties. In chicken, the Golgin subfamily B member 1 (GOLGB1) gene, which locates on chromosome 1, encodes the coat protein 1 vesicle inhibiting factor. A previous study showed that the 65-bp insertion/deletion in the GOLGB1 gene was significantly associated with chicken body weight, neck weight, abdominal fat weight, abdominal fat percentage and the yellow index b of the breast in Chinese indigenous chicken (N409-breed). In this study, 65-bp indel polymorphism in the GOLGB1gene was evaluated in association with body weight in Noi chickens. The live body weight of 170 chickens (90 females, 80 males) at continuous ages of 7-day intervals (from 28 to 84 days) was recorded. A 65-bp indel polymorphism in the GOLGB1 gene was analyzed using the PCR method. The results of PCR and sequencing revealed two alleles (I and D) corresponding to three genotypes: II, ID, DD, in which, the I allele appears with the highest frequency (0.79) in the studied population. An association study using Minitab software showed that genotype was significantly associated with body weight in Noi chickens at days 35 to 84 (P < 0.05). Individuals with more allele “I” have higher live body weight than others. Both factors (sex and genotype) simultaneously affected the body weight of Noi chickens. The results of this study suggested that the 65-bp indel in the GOLGB1 gene could be considered a potential marker for Noi chicken breeding.